2008
DOI: 10.1159/000138335
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Autoimmunity: The Paradigm of Primary Biliary Cirrhosis – A Mini-Review

Abstract: The incidence of autoimmune diseases appears to be increasing in virtually every population. This is well illustrated by primary biliary cirrhosis, a disease characterized by an immune response to small bile ducts and an incidence increasing with age. The etiology of primary biliary cirrhosis remains enigmatic, although there is clearly an interplay of genetics and environment with a possible role for immunosenescence. The increasing usage of serologic tests for the hallmark of primary biliary cirrhosis, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In autoimmune hepatitis, these are α-smooth muscle actin, liver kidney microsomal antigens, and soluble liver/liver pancreas-or liver-cytosol-specific antigens (102). In primary biliary cirrhosis, the multienzyme 2-Oxo-acid dehydrogenase complex contains the culprit autoantigens (103).…”
Section: Nonalcoholic Liver Fibrosismentioning
confidence: 99%
“…In autoimmune hepatitis, these are α-smooth muscle actin, liver kidney microsomal antigens, and soluble liver/liver pancreas-or liver-cytosol-specific antigens (102). In primary biliary cirrhosis, the multienzyme 2-Oxo-acid dehydrogenase complex contains the culprit autoantigens (103).…”
Section: Nonalcoholic Liver Fibrosismentioning
confidence: 99%
“…The age at presentation in the last years is around 60 years, but many patients are over 65 at onset of the disease [63]. Several prognostic models for PBC have confirmed that increasing age does have an independent and adverse effect on prognosis [64], implying that the natural history in elderly subjects may be worse.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
“…Primary biliary chirrosis (PBC) [77] and autoimmune cholangitis (AIC) are autoimmune liver diseases affecting biliary ductular cells. In predicting the immunodominant epitope of the pyruvate dehydrogenase complex E2 in PBC [78], phagotopes were selected from RPLs with PBC sera and shown to be reactive by capture ELISA with antibodies affinity purified on the E2 subunit of the pyruvate dehydrogenase complex (PDC-E2) [79].…”
Section: Primary Biliary Cirrhosis and Autoimmune Cholangitismentioning
confidence: 99%